Analisis Fiqh Siyasah Terhadap Kampanye Pemilihan Umum Di Media Sosial Berdasarkan Peraturan Komisi Pemilihan Umum Nomor 23 Tahun 2018 Tentang Kampanye Pemilihan Umum - Muhammad Fadhli (Ma'had Aly Raudhatul Ma'arif, 2023)
Based on the General Election Commission Regulation (PKPU) of the Republic of Indonesia No. 23 of 2018 on Election Campaigns, Article 35 paragraphs 1 to 4 regulates campaigns on social media. Paragraph 1 states,